2017
DOI: 10.1039/c7ob00458c
|View full text |Cite
|
Sign up to set email alerts
|

New selenosteroids as antiproliferative agents

Abstract: Starting from natural steroids (diosgenin, hecogenin, smilagenin, estrone), we have prepared a wide panel of selenoderivatives, including benzoselenazolones, selenosemicarbazones, isoselenocyanates, selenoureas, selenocyanates and diselenides, with the aim of developing new families of potential chemotherapeutic agents. The modification of the organoselenium moieties, and their position on the steroid provided valuable information concerning the antiproliferative activities. Among all the families accessed her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…When evaluating the GPx-like activity of a group of selenosteroids ( 26 and 27 , among others), Fuentes-Aguilar et al [ 67 ] found that the GPx-like activity was under that of ebselen for all the compounds considered.…”
Section: Selenides and Diselenides With Therapeutic Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…When evaluating the GPx-like activity of a group of selenosteroids ( 26 and 27 , among others), Fuentes-Aguilar et al [ 67 ] found that the GPx-like activity was under that of ebselen for all the compounds considered.…”
Section: Selenides and Diselenides With Therapeutic Perspectivementioning
confidence: 99%
“…For estrone and diosgenin-based diselenides ( 26 and 27 ) , the in vitro antiproliferative activity against a panel of six human solid tumor cell lines, when tested up to a 100 µM concentration, was negligible [ 67 ]. Cancer cell lines included non-small cell lung (A549 and SW1573), breast (HBL-100 and T-47D), cervix (HeLa) and colon (WiDr) [ 67 ].…”
Section: Selenides and Diselenides With Therapeutic Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Literature reveals that besides the inversion of C-13, the introduction of an amino group onto C-2 or C-4 of estrone also leads to significant decreases in its binding affinity for nuclear estrogen receptors (ERα and ERβ) [ 28 ]. Certain derivatives of 2- or 4-aminoestrone or their 3-methyl ether possess diverse biological activities, including enzyme inhibitory or antiproliferative properties [ 1 – 3 29 30 ]. The 17β-HSD1 enzyme is responsible for the reduction of estrone into 17β-estradiol, which may enhance the proliferation of tumor cells [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…To increase the activity and selectivity of ebselen, various modifications of its structure were efficiently conducted by several research groups. Promising results exposed the significant potential in this field of organoselenium chemistry [15][16][17][18][19]. However, there are only few examples of derivatives bearing a sulfur atom in the place of oxygen [20].…”
Section: Introductionmentioning
confidence: 99%